Judy Moody and Friends : Jessica Finch In Pig Trouble - McDonald, Megan; Madrid, Erwin; Reynolds, Peter, 1961- (Somerville, Mass. : Candlewick Press, 2014)
With her birthday coming up, Jessica hopes that, just maybe, her present will be a real-live potbellied pig. Jessica can hardly wait for her party with Judy Moody and all their friends. But Judy Moody is acting like a pig-head, and Jessica UN-invites her from the party. To make matters worse, Jessica has snooped around the house and has found zero sign of a pig present. Could her birthday be any more of a disaster?
Just say 'oink' -- This little piggy -- The PeeGee WeeGee Club.
Keywords: Moody, Judy (Fictitious character) -- Juvenile fiction; Friendship -- Juvenile fiction; Birthdays -- Juvenile fiction; Birthday parties -- Juvenile fiction; Moody, Judy (Fictitious character) -- Fiction; Friendship -- Fiction; Birthdays -- Fiction; Birthday parties -- Fiction; Juvenile fiction